Human monkeypox coinfection with syphilis in an immunocompromised patient - Irvin Ordoñez-González; Berenice López-Zamora; Gabriela Medina; Geraldine Vanessa Reyes-Navarro; Alberto Ordinola Navarro; María Pilar Cruz-Domínguez; Olga Vera-Lastra; Miguel Ángel Saavedra (PAGEPress Publications, 2022)
Monkeypox is a viral zoonoses from the Poxviridae family that spreads at an unprecedented rate. It is transmitted through contact with skin lesions, respiratory droplets, body fluids, and sexual contact. The diverse presentation of disease leads to misdiagnosis. Thus, clinicians should have a high index of suspicion, mainly with diseases with skin lesions. The most vulnerable group to developing this disease are individuals with risky sexual relationships, sexually transmitted infections or human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). To date, only one case of coinfection with monkeypox virus, syphilis, and HIV has been reported; however, no cases have been revealed in the Mexican territory. Herein we describe an unusual case of Syphilis-Monkeypox coinfection in an immunocompromised patient; despite his coinfections, he had a favorable prognosis. Furthermore, we attach allusive pictures of the natural evolution of dermatological lesions.